Agrobiodiversity as Necessary Standard for the Design and Management of Sustainable Farming Systems - Borsari, Bruno (PLANTA TROPIKA, 2022)
Agriculture constitutes the major planetary force, which over the course of the past century has been changing forever the connotations of terrestrial ecosystems, due to its dependence on resources and impacts (e.g.: global climate change, biodiversity loss, pollution, and eutrophication of fresh and coastal waters). The purpose of this work aimed at demonstrating the compelling need to design and manage modern farms in a way that these may conserve, and even foster biodiversity because its restoration offers resilience, longevity, and productivity to 21st century farms. Therefore, special emphasis in this work was given to the management of agricultural soils and agroforestry. These approaches enhance biological diversity, while strengthening the health of plants, animals, and human communities thus, contributing to the health of planet Earth. Agroecology is the science, practice and social movement that effectively, can assist with a conversion of farming systems toward sustainability and a restoration of agrobiodiversity.